Antibody persistence in the first 6 months following SARS-CoV-2 infection among hospital workers: a prospective longitudinal study. (May 2021) - L'Huillier, Arnaud G.; Meyer, Benjamin; Andrey, Diego O.; Arm-Vernez, Isabelle; Baggio, Stephanie; Didierlaurent, Arnaud; Eberhardt, Christiane S.; Eckerle, Isabella; Grasset-Salomon, Carole; Huttner, Angela; Posfay-Barbe, Klara M.; Royo, Irene Sabater; et al.
Abstract: Objectives: To evaluate longitudinally the persistence of humoral immunity for up to 6 months in a cohort of hospital employees with mild coronavirus disease 2019 (COVID-19). Methods: We measured anti-RBD (receptor binding domain of viral spike protein), anti-N (viral nucleoprotein) and neutralizing antibodies at 1, 3 and 6 months after mostly mild COVID-19 in 200 hospital workers using commercial ELISAs and a surrogate virus neutralization assay. Results: Antibodies specific for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) persisted in all participants for up to 6 months. Anti-RBD geometric mean concentrations (GMCs) progressively increased between months 1 (74.2 U/mL, 95%CI: 62.7–87.8), 3 (103.2 U/mL, 95%CI: 87.9–121.2; p < 0.001), and 6 (123.3 U/mL, 95%CI: 103.4–147.0; p < 0.001) in the whole cohort. Anti-N antibodies were detectable in >97% at all times. Neutralizing antibodies were detectable in 99.5% of participants (195/196) at 6 months post infection. Their GMC progressively decreased between months 1 (20.1 AU/mL, 95%CI: 16.9–24.0), 3 (15.2 AU/mL, 95%CI: 13.2–17.6; p < 0.001) and 6 (9.4 AU/mL, 95%CI: 7.7–11.4; p < 0.001). RBD-ACE2-inhibiting antibody titres and anti-RBD antibody concentrations strongly correlated at each timepoint (all r > 0.86, p < 0.001). Disease severity was associated with higher initial anti-RBD and RBD-ACE2-inhibiting antibody titres, but not with their kinetics. Conclusions: Neutralizing antibodies persisted at 6 months in almost all participants, indicating more durability than initially feared. Anti-RBD antibodies persisted better and even increased over time, possibly related to the preferential detection of progressively higher-affinity antibodies.